Relict and contemporary soils on uplifted marine terraces of Kvartsittsletta, SW Spitsbergen - Korabiewski, Bartosz (Polish Polar Research, 2023)
The soils of Arctic regions are of great interest due to their high sensitivity to climate change. Kvartsittsletta coast in the vicinity of the Baranowski Research Station of the University of Wrocław constitutes a sequence of differently aged sea terraces covered with different fractions of beach material. It is a parent material for several developing soil types. Despite the low intensity of the modern soil-forming processes, the soil cover is characterized by high diversity. Soil properties are formed mainly by geological and geomorphological factors, which are superimposed by the influence of climate and living organisms. The degree of development of soil is usually an indicator of its relative age. This article highlights the dominant influence of lithology and microrelief over other soil-forming factors, including the duration for which the parent material was exposed to external factors. The soils on the highest (oldest) terrace steps of the Kvartsittsletta rarely showed deep signs of soil-forming processes other than cryoturbations. On the youngest terraces, deep-reaching effects of soil processes associated with a relatively warm climate, including the occurrence of cambic horizons, were observed. Their presence in Arctic regions carries important environmental information and may be relevant to studies of climate change.